2017
DOI: 10.5152/turkjsurg.2017.3670
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to reduce the surgical mortality and morbidity of peptic ulcer perforations?

Abstract: INTRODUCTIONWith regard to creating a novel vision for former diseases, our memorizationsshould be updated. Some diseases and their outcomes, which have been previously very well known, are nowadays almost always presented as unexpected cases because of new technologies and evolvements in medicine due to resistant events. Thus, antiulcer medication and presentation of elderly patients have changed in peptic ulcer perforation (PUP) and, transforming the patient profiles with PUP in our era. Therefore, a novel v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Few patients could not be revived even after ventilatory support. Adequate fluid resuscitation & ensuring satisfactory urine output before shifting the patient to surgery especially in patients with raised serum creatinine levels has cut down mortality from 9.8% in study conducted by Hut A et al [7] , and 9% in Lohsiriwat V [9] study to 5% in our study. Therefore, giving considerable attention to age and concomitant diseases, an aggressive pre operative resuscitation from shock, satisfactory urine output, avoiding delay in surgery, good surgical technique, thorough peritoneal lavage and meticulous post-operative care including chest physiotherapy is needed to improve overall results.…”
Section: Observationmentioning
confidence: 44%
See 4 more Smart Citations
“…Few patients could not be revived even after ventilatory support. Adequate fluid resuscitation & ensuring satisfactory urine output before shifting the patient to surgery especially in patients with raised serum creatinine levels has cut down mortality from 9.8% in study conducted by Hut A et al [7] , and 9% in Lohsiriwat V [9] study to 5% in our study. Therefore, giving considerable attention to age and concomitant diseases, an aggressive pre operative resuscitation from shock, satisfactory urine output, avoiding delay in surgery, good surgical technique, thorough peritoneal lavage and meticulous post-operative care including chest physiotherapy is needed to improve overall results.…”
Section: Observationmentioning
confidence: 44%
“…~ 137 ~ group with mortality was significantly higher than that of the morbidity, and the mean age of the morbidity group was significantly higher than that of the no complication group. Sivaram P et al [3] , Bojananpu S et al [5] and several other studies have reported that patients aged 65 years or more have significantly higher rates of mortality compared with younger patients [7,8,12,13] . similar to our study and this finding is believed to be due to the increased incidence of accompanying diseases in the elderly patients.…”
Section: Observationmentioning
confidence: 94%
See 3 more Smart Citations